Low Transforming Growth Factor-β Pathway Activity in Cervical Adenocarcinomas - Marvin, Dieuwke L.; Spaans, Vivian M.; de Kroon, Cor D.; Slieker, Roderick C.; Khelil, Maryam; ten Dijke, Peter; Ritsma, Laila; Jordanova, Ekaterina S. (Frontiers in Oncology, 2022)
Cervical cancer is the fourth most common cancer in women worldwide. Squamous cell carcinoma (SCC) and adenocarcinoma (AC) are the most common histological types, with AC patients having worse prognosis. Over the last two decades, incidence rates of AC have increased, highlighting the importance of further understanding AC tumorigenesis, and the need to investigate new treatment options. The cytokine TGF-β functions as a tumour suppressor in healthy tissue. However, in tumour cells this suppressive function can be overcome. Therefore there is an increasing interest in using TGF-β inhibitors in the treatment of cancer. Here, we hypothesize that TGF-β plays a different role in SCC and AC. Analysis of RNA-seq data from the TCGA, using a TGF-β response signature, resulted in separate clustering of the two subtypes. We further investigated the expression of TGF-β-signalling related proteins (TβR1/2, SMAD4, pSMAD2, PAI-1, αvβ6 and MMP2/9) in a cohort of 62 AC patients. Low TβR2 and SMAD4 expression was associated with worse survival in AC patients and interestingly, high PAI-1 and αvβ6 expression was also correlated with worse survival. Similar correlations of TβR2, PAI1 and αvβ6 with clinical parameters were found in previously reported SCC analyses. However, when comparing expression levels between SCC and AC patient samples pSMAD2, SMAD4, PAI-1 and αvβ6 show lower expression in AC compared to SCC. Because of the low expression of core TβR1/2, (p-)SMAD2 and SMAD4 proteins and the correlation with worse prognosis, TGF-β pathway most likely leads to tumour inhibitory effects in AC and therefore the use of TGF-β inhibitors would not be recommended. However, given the correlation of PAI-1 and αvβ6 with poor prognosis, the use of TGF- β inhibitors might be of interest in SCC and in the subsets of AC patients with high expression of these TGF- β associated proteins.